2018
DOI: 10.3390/resources7040088
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Metal Ore Grades—Is the Fear of Resource Depletion Justified?

Abstract: Metals are an essential part of modern living. Ensuring the future supply of metals is a key issue in politics, science, and economics because the available amount of mineral resources is limited. To measure the depletion of mineral resources, several indicators are used. Some of them are based on the ore grade, which has been decreasing over time and is thus taken as a sign of resource exhaustion. However, does this assumption hold true? This paper shows that the development of ore grades is mainly the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 26 publications
(39 reference statements)
0
32
0
Order By: Relevance
“…This can be done by adjusting the ore grade. If, however, the mill head grade is used, which is often the basis for a discussion of the decreasing ore grades [12], dilution is already included. In this paper, we define the ore grade as the mill head grade, because it represents the average mined ore grade and is often referred to in publications.…”
Section: Miningmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be done by adjusting the ore grade. If, however, the mill head grade is used, which is often the basis for a discussion of the decreasing ore grades [12], dilution is already included. In this paper, we define the ore grade as the mill head grade, because it represents the average mined ore grade and is often referred to in publications.…”
Section: Miningmentioning
confidence: 99%
“…Even if rising demand is the driving force, it cannot be said with certainty that there will be mining of lower ore grades. There are still deposits with higher ore grades [12,51], although a decrease seems to be more likely since a higher demand offers potentials for economies of scale and further technological improvements [52,53].…”
Section: Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem with this approach, according to experts in the mining industry, is "that grades have so far been of limited relevance to the issue of availability" ( [16], Section 10). There are many different arguments for this statement (see also an analysis on this issue [23]).…”
Section: Resource Scarcity In the Classic Environmental Life-cycle Asmentioning
confidence: 99%
“…The experience over the last couple of centuries has been that new discoveries or increases in economic reserves have caused long-term average ore grades to decline. As technologies have changed, new economic reserves have been discovered and others extended to lower-grade zones resulting in declines in the average grade of ore that has been mined and processed (Rötzer and Schmidt 2018). The grade to volume relationship for individual porphyry copper deposits is exponential, which is also part of the reason why head grades are inversely related to the tonnage of ore mined (Crowson 2011a, Northey et al 2018) and ore grade declines have been accompanied by large increases in identified reserves.…”
Section: What Is Known?mentioning
confidence: 99%